Pelaksanaan Tugas Dan Wewenang Badan Pengawas Pemilu (Bawaslu) Dalam Mencegah Politik Uang Pada Pemilu 2024 (Studi Kasus Kabupaten Manggarai Barat) - Bahagia, Yovita; Monteiro, Yosef M; Dalima, Maria Susanti (Artemis Law Journal, 2025)
This study aims to analyze the effectiveness of the Election Supervisory Agency (Bawaslu) of West Manggarai Regency in preventing the practice of money politics in the 2024 Election. The method used is empirical juridical with a socio-legal, conceptual, and legislative approach, involving interviews with stakeholders The results of the study indicate that Bawaslu faces various internal challenges, such as limited human resources (4 district apparatus and 36 sub-district supervisors to supervise 181 regions), minimal APBD budget, and weaknesses in regulations, especially Law No. 7/2017 which does not provide sanctions for recipients of money politics. external challenges include the deep-rooted culture of money politics, low legal awareness in the community - as seen from the acceptance of money or "water suction machines" by residents of Golo Ketak Village - and economic limitations. Although Bawaslu has implemented prevention strategies, such as vulnerability mapping (IKP) and cross-agency coordination, the implementation of these strategies is still not optimal, especially due to disparities in the reach of socialization in remote areas. For this reason, this study recommends: (1) revision of the Election Law to expand criminal sanctions, (2) strengthening the capacity of Bawaslu through the addition of human resources and budget increases, and (3) implementation of massive community-based education.